Porosity Analysis of Acacia catechu Seed-derived Carbon Materials Activated with Sodium Hydroxide and Potassium Hydroxide: Insights from Methylene Blue and Iodine Number Methods - Mishra, Pawan Kumar; Aryal, Sabin; Oli, Hari Bhakta; Shrestha, Timila; Jha, Dhirendra; Shrestha, Ram Lal; Bhattarai, Deval Prasad (Journal of Nepal Chemical Society, 2025)
The significant adsorption capacity of activated carbon makes it a highly effective adsorbent material. The choice of activating chemicals plays a crucial role in determining the surface morphology and pore size distribution of the resulting activated carbon. In this study, potassium hydroxide and sodium hydroxide were employed as chemical activating agents in the preparation of activated carbon from the waste biomass of Acacia catechu seeds through a carbonization process. Fourier-transform infrared spectroscopy (FTIR) was utilized to examine the surface functional groups, while X-ray diffraction (XRD) analysis provided insights into the crystallinity of the activated carbons. Field-Emission Scanning Electron Microscopy (FESEM) was employed to analyze surface morphology. For the adsorption capacity assessment, methylene blue number (MBN) and iodine number (IN) method were employed. The activated carbon derived using KOH-activator (ACSK-6) exhibited higher iodine number (1269.62 mg/g) and methylene blue number (238.62 mg/g) compared to activated carbon synthesized using NaOH (ACSN-6). The well-developed porosity and superior adsorption capacity of the ACSK-6 sample underscore its potential in various application.